CPAP improves endothelial function in patients with minimally symptomatic OSA: results from a subset study of the MOSAIC trial. - Kohler, M; Craig, S; Pepperell, J; Nicoll, D; Bratton, D; Nunn, A; Leeson, P; Stradling, JR (2013)
BACKGROUND: Minimally symptomatic OSA is a highly prevalent disorder, and the effects of CPAP on vascular function in these patients are unknown. This trial aimed to investigate whether CPAP improves vascular function in minimally symptomatic OSA. METHODS: In two centers taking part in the MOSAIC (Multicentre Obstructive Sleep Apnoea Interventional Cardiovascular) trial, 253 patients with minimally symptomatic OSA were randomized to 6 months of CPAP or standard care. Two hundred eight patients attended their follow-up visit within the predefined time window and had complete measurements of arterial stiffness (augmentation index [AIx]), and 64 patients had endothelial function measurements by brachial artery flow-mediated dilatation (FMD). Multivariable analyses adjusting for baseline measurements and minimization factors were performed to assess the effect of CPAP treatment on FMD (% dilatation) and AIx (% augmentation) compared with standard care. RESULTS: The mean ± SD baseline oxygen desaturation index and Epworth Sleepiness Score (ESS) of the 208 patients (age 58 ± 7.3 years, 31 women) were 13.7 ± 12.8 events/h and 8.3 ± 4.2, respectively. There was no CPAP treatment effect on arterial stiffness (AIx, -1.4%; 95% CI, -3.6 to +0.9%; P = .23), but CPAP improved endothelial function (FMD, +2.1%; 95% CI, +1.0 to +3.2%; P andlt; .0001). CPAP reduced daytime sleepiness (ESS, -2.2; 95% CI, -3.0 to -1.5; P andlt; .0001) compared with standard care. There was a larger improvement in FMD in patients using CPAP for andgt; 4 h/night than those who used it less (P = .013). CONCLUSIONS: CPAP improves endothelial function, but not arterial stiffness, in minimally symptomatic OSA. Thus, minimally symptomatic OSA may be a cardiovascular risk factor. TRIAL REGISTRY: ISRCTN Register; No.: ISRCTN 34164388; URL: http://isrctn.org.